Numerical 3D modelling of oil dispersion in the sea due to different accident scenarios. (September 2017) - Guandalini, Roberto; Agate, Giordano; Moia, Fabio
Abstract: The study describes the development of a methodology to evaluate the dynamics related to the dispersion of hydrocarbons in the sea and the consequent environmental impact. The 3D numerical model was applied to hypothetical spill scenarios due to platform or floating vessel accidents. It was able to account for the complexity of the sea system involved in the dispersion process (meteorology, marine and morphological conditions). The scenarios analyzed consider both loss release events (low intensity for long time) and serious accident events (strong intensity for short time), seeking out the hydrocarbons diffusion in the sea.